The Ability To Run A Short Distance Of 40 Meters In Class V and VI Students of Inpres Bontosunggu Primary School, Gowa District - Suriah Hanafi (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
This research aims to obtain answers to problems regarding the 40-meter running ability level of students at SD Inpres Bontosunggu, Gowa Regency. The population of this research was students at SD Inpres Bontosunggu, Gowa Regency, using a sample of all members of the population of 40 male students (23 students in class V and 17 students in class VI). This type of research is quantitative descriptive research using a survey method by carrying out tests and measurements directly on a predetermined sample. They standardized a 40-meter running ability test instrument from the Indonesian Physical Fitness Test (TKJI, 2010). Data analysis uses descriptive percentage analysis techniques. From statistical calculations it is known that there are 5 students (12.5%) in the "Very High" category, there are 6 students (15.0%) in the "High" category, there are 12 students (30.0%) in the "Medium" category, There are 14 (35.0%) in the "Low" category and there are 3 students (7.5.0%) in the "Very poor" category. Overall, the research results show that most of the 40-meter running abilities of the students at SD Inpres Bontosunggu, Gowa Regency show abilities in the "Low" category.